(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article explores how the concept of equality is affected by the technological developments in healthcare, focusing on AI. In this regard, the article develops that in AI healthcare systems ensuring data quality is pivotal when trying to ensure the implementation of the principle of equality. Analysing the European Commission’s proposed AI Act, we highlight how horizontal rules, coupled with standardisation, can achieve data quality in AI based healthcare technologies. The article concludes with a reflection on remaining grey areas that require further elaboration by the European legislator.